Edukasi Pentingnya Menghadapi Psikologi Ibu Terhadap Kesiapan Fisik Dan Mental Ibu Dalam Mempersiapkan Persalinan Pada Ibu Hamil Trimester III - Septiana Arpen, Ratih; Afnas, Nur Hidayah; Silvia, Elwitri; Ulya, Rahmatul (Universitas Sumatera Barat, 2024)
Psychological preparation One thing that mothers must prepare before giving birth is to avoid panic and fear and be calm, so that pregnant women can go through the birthing period well and be more prepared and ask for support from the people closest to them. Mothers who are not ready to face childbirth are one of the factors causing maternal mortality (MMR). Many efforts have been made to support efforts to reduce MMR, one of which is by preparing for childbirth starting during pregnancy. From the initial survey at the service location, namely Poskeskel Pakan Kurai Bukitinggi, several problems were found, especially the problems of pregnant women, one of which was the problem of dealing with maternal psychology regarding the physical and mental readiness of mothers in preparing for childbirth in the third trimester of pregnant women from 11 pregnant women who were accompanied by health cadres. Of the 6 pregnant women, in discussions with pregnant women, several problems were raised, one of which was the problem of pregnant women's lack of knowledge about how to prepare for the birthing process. At the activity stage, there will be introduction, education provided directly to pregnant women, guidance and outreach to pregnant women. Evaluation is carried out by providing questions and answers. The results of this activity are the provision of education and the existence of leaflets which are directly read by pregnant women. There is an increase in mothers' knowledge about pregnancy preparation which includes dealing with maternal psychology regarding physical and mental readiness in preparing for childbirth. With increased knowledge, a positive attitude will be formed from pregnant women to prepare for childbirth.